A checklist to improve health system resilience to infectious disease outbreaks and natural hazards. Issue 8 (5th August 2020) - Meyer, Diane; Bishai, David; Ravi, Sanjana J; Rashid, Harunor; Mahmood, Shehrin Shaila; Toner, Eric; Nuzzo, Jennifer B
Abstract : Recent infectious disease outbreaks, including the ongoing global COVID-19 pandemic and Ebola in the Democratic Republic of the Congo, have demonstrated the critical importance of resilient health systems in safeguarding global health security. Importantly, the human, economic and political tolls of these crises are being amplified by health systems' inabilities to respond quickly and effectively. Improving resilience within health systems can build on pre-existing strengths to enhance the readiness of health system actors to respond to crises, while also maintaining core functions. Using data gathered from a scoping literature review, interviews with key informants and from stakeholders who attended a workshop held in Dhaka, Bangladesh, we developed a Health System Resilience Checklist ('the checklist'). The aim of the checklist is to measure the specific capacities, capabilities and processes that health systems need in order to ensure resilience in the face of both infectious disease outbreaks and natural hazards. The checklist is intended to be adapted and used in a broad set of countries as a component of ongoing processes to ensure that health actors, institutions and populations can mount an effective response to infectious disease outbreaks and natural hazards while also maintaining core healthcare services. The checklist is an important first step in improving health system resilience to these threats, but additional research and resources will be necessary to further refine and prioritise the checklist items and to pilot the checklist with the frontline health facilities that would be using it. This will help ensure its feasibility and durability for the long-term within the health systems strengthening and health security fields.